The blue straggler V106 in NGC 6791: a prototype progenitor of old single giants masquerading as young. Issue 4 (18th September 2018) - Brogaard, K; Christiansen, S M; Grundahl, F; Miglio, A; Izzard, R G; Tauris, T M; Sandquist, E L; VandenBerg, D A; Jessen-Hansen, J; Arentoft, T; Bruntt, H; Frandsen, S; et al.
ABSTRACT: We determine the properties of the binary star V106 in the old open cluster NGC 6791 . We identify the system to be a blue straggler cluster member by using a combination of ground-based and Kepler photometry and multi-epoch spectroscopy. The properties of the primary component are found to be M_p1.67 M_, more massive than the cluster turn-off, with R_p1.91 R_ and T eff = 7110 ± 100 K. The secondary component is highly oversized and overluminous for its low mass with M_s0.182 M_, R_s0.864 R_, and T eff = 6875 ± 200 K. We identify this secondary star as a bloated (proto) extremely low-mass helium white dwarf. These properties of V106 suggest that it represents a typical Algol-paradox system and that it evolved through a mass-transfer phase, which provides insight into its past evolution. We present a detailed binary stellar evolution model for the formation of V106 using the mesa code and find that the mass-transfer phase only ceased about 40 Myr ago. Due to the short orbital period ( P = 1.4463 d), another mass-transfer phase is unavoidable once the current primary star evolves towards the red giant phase. We argue that V106 will evolve through a common-envelope phase within the next 100 Myr and merge to become a single overmassive giant. The high mass will make it appear young for its true age, which is revealed by the cluster properties. Therefore, V106 is potentially a prototype progenitor of old field giants masquerading as young.